Penerapan Media Pebelajaran Realia Pada Materi IPAS Untuk Meningkatakan Hasil Belajar Siswa - Moji, Erlina; Andi Nurwati; Zohrawaty Hiola (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This research was conducted in two cycles. To observe the learning outcomes of IPAS students in grade IV at SDN 9 Limboto, four stages were carried out according to Kemmis and McTaggart, namely: planning, implementation, observation, and reflection. The subjects of this research included 16 grade IV students, employing Realia learning media in the IPAS subject. From the implementation of Realia learning media, it was generally obtained that student learning outcomes in the IPAS subject, which initially was 56% experienced an increase of 88% in grade IV. This was based on the results of observations and pretest and posttest results due to (a) students enjoying the application of Realia learning media, which they considered new and had not encountered before, and (b) the learning material discussed was relatively comprehensible for the students because the researcher presented it concisely yet clearly and engagingly. The test results conducted in each cycle showed improvement. The Post Test of Cycle I had a mastery percentage of 50%, while the Post Test of Cycle II also had a mastery percentage of 50%. The average score for the Cycle I test questions was 65.92, with a mastery percentage of 56%, up to the Cycle II test questions, which had an average score of 79.84 and a mastery percentage of 88%